2022
DOI: 10.1113/jp282884
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of computational models for the design of spinal cord stimulation therapies: from neural circuits to patient‐specific simulations

Abstract: Seventy years ago, Hodgkin and Huxley published the first mathematical model to describe action potential generation, laying the foundation for modern computational neuroscience. Since then, the field has evolved enormously, with studies spanning from basic neuroscience to clinical applications for neuromodulation. Computer models of neuromodulation have evolved in complexity and personalization, advancing clinical practice and novel neurostimulation therapies, such as spinal cord stimulation. Spinal cord stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…placement relative to the spinal cord midline) and utilizing lookup tables of optimized parameters for the situation that best matches the conditions for the individual patient. Furthermore, these sources of intrapatient variability can be accounted for in patient-specific computational models [14,34,67,68] in which we can then apply our optimization framework to determine optimal patient-specific stimulation parameters. It is also important to recognize that the application of our optimization framework is not limited to chronic pain management using SCS.…”
Section: Discussionmentioning
confidence: 99%
“…placement relative to the spinal cord midline) and utilizing lookup tables of optimized parameters for the situation that best matches the conditions for the individual patient. Furthermore, these sources of intrapatient variability can be accounted for in patient-specific computational models [14,34,67,68] in which we can then apply our optimization framework to determine optimal patient-specific stimulation parameters. It is also important to recognize that the application of our optimization framework is not limited to chronic pain management using SCS.…”
Section: Discussionmentioning
confidence: 99%
“…1) The conventional quasi-static assumption in neuromodulation regarding the physics of current passage through macroscopic tissue [36]- [38], including SCS [39], leading to the governing Laplace equation. The electric field generated in the spinal cord by SCS is a function of the stimulation dose (electrode position, current) and the anatomy/macroscopic tissue properties [40].…”
Section: General Approach and Quasi-uniform-mirror Rationalementioning
confidence: 99%
“…To test this, we have used epidural electrodes to pair motor cortex stimulation with dorsal (sensory) spinal cord stimulation in rats. Epidural spinal cord stimulation recruits a large number of sensory axons as they enter the spinal cord (Capogrosso et al 2013; Liang et al 2023; McIntosh et al 2023). In one preclinical study, our group showed that timing motor cortex and dorsal epidural spinal stimulation to converge in the spinal cord markedly increased the motor evoked potential (MEP) (by 155%), while convergence in motor cortex resulted in a much smaller effect (17%) (Pal et al 2022).…”
Section: Introductionmentioning
confidence: 99%